Exogenous Application of Gibberellic Acid, Salicylic Acid, and Calcium Chloride on Physical Properties and Shelf Life of Tomato - Dhital, Priya; Rauniyar, Krish; Mahat, Samikshya (Nepalese Journal of Agricultural Sciences, 2025)
The study was conducted from May 2nd to June 19th of 2024 at HICAST, Kirtipur. A Completely Randomized Design (CRD) comprising ten treatments with three replications was executed to evaluate the physical characteristics and shelf life of tomato fruits of the ‘Srijana’ variety treated with GA3(O.1%, 0.2%, and 0.3%), CaCl2 (0.5%, 1%, and 1.5%), and SA (0.1mM, 0.2mM and 0.3mM). The statistical analysis of data was completed using GenStat and Microsoft Excel. The quality parameters were evaluated after 15 days of storage and 25 days of storage. All the tested treatments were stored at an average room temperature of 26.9±2 °C (dry) and 20.5±2 °C (wet). They showed a significant delay in weight loss and spoilage percentage in treated tomato fruits compared to the control set. GA3 treatments were the most effective, with 0.1% of GA3 (T1) resulting in the least spoilage (34.1%), reduced weight loss (17.85%), the highest firmness (1.5 kg/cm2), and the longest possible extension of the average shelf life to 29 days. With the increasing storage period, the ripening progressed, marked by the declining values of firmness on the 25th day. A particularly noteworthy observation is that the higher concentrations of CaCl2 (1.5%) provided significantly better results than lower concentrations (0.5% and 1%). 0.3 mM of SA was more effective than lower concentrations, though higher concentrations might yield even better outcomes.